2007
DOI: 10.1136/bjo.2006.113399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine on retinal and choroidal blood flow parameters in humans

Abstract: Aim: To investigate the effect of dopamine on retinal and choroidal blood flow in humans. Methods: We investigated the effect of two doses of intravenous dopamine (5 and 10 mg/kg/min) via a randomised double-masked crossover study in 12 healthy subjects chosen from a total of 16. Blood flow parameters in retina, optic nerve head and choroid were assessed with bi-directional laser Doppler velocimetry, laser Doppler flowmetry and laser interferometric measurement of fundus pulsation amplitude, respectively. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
7
0
4
Order By: Relevance
“…Nitric oxide has also been shown to play a role in the regulation of choroidal blood flow during isometric exercise (Luksch et al. 2003), light−dark transitions (Huemer et al. 2007) and in the flicker‐induced vasodilator response in the retina (Dorner et al.…”
Section: Endothelial Function In the Eyementioning
confidence: 99%
“…Nitric oxide has also been shown to play a role in the regulation of choroidal blood flow during isometric exercise (Luksch et al. 2003), light−dark transitions (Huemer et al. 2007) and in the flicker‐induced vasodilator response in the retina (Dorner et al.…”
Section: Endothelial Function In the Eyementioning
confidence: 99%
“…95 According to Witkovsky, 97 dopamine is released by a unique set of amacrine cells and activates D1 and D2 dopamine receptors distributed throughout the retina, where it plays as a chemical messenger for light adaptation and multiple trophic capabilities. 96 These findings were supported by Huemer et al, 98,99 who indicated that dopamine has a distinct effect on retinal vessel diameters, which implies a role of dopamine in retinal blood flow hemodynamics. However, other studies 100,101 show that the effect of dopamine would take place mainly at the cortical level.…”
Section: Carbidopa-levodopamentioning
confidence: 69%
“…Следующий наружный ядерный слой образован ядрами фоторецепторов, после которого следует наружный плексиформный слой, расположенный между наружным и внутренним ядерными слоями. [20][21][22] Радужка: адреналин, норадреналин, α 1адренорецепторы [26][27][28] Хрусталик: предшественник дофамина (ДОФА), β 2адренорецепторы [38][39][40] Цилиарное тело: [26,28,29] Слеза: адреналин, норадреналин, дофамин, метаболиты дофамина (ДОФУК, ГВК) [23][24][25] Влага: адреналин, норадреналин, дофамин, метаболит дофамина (ДОФУК) [19] Склера: D1-рецепторы к дофамину [30] Стекловидное тело: норадреналин, адреналин, дофамин, метаболит дофамина (ДОФУК) [31] Хориоидея: [32] Зрительный нерв: D1-и D2-рецепторы к дофамину [33,34] Сетчатка: адреналин, норадреналин, дофамин, α 1 -адренорецепторы, D1-и D2-рецепторы к дофамину [35][36][37] Рис. [14,18,46].…”
Section: сетчаткаunclassified
“…Практически во всех клетках сетчатки обнаружены рецепторы к дофамину [47,48]. Кроме того, ДА синтезируется во многих клетках сетчатки -фоторецепторах, амакриновых, биполярных, интерплексиформных и горизонтальных клетках [32,[35][36][37]49]. Наибольшее содержание ДА обнаружено в амакриновых клетках, которые участвуют в передаче импульса в горизонтальном направлении от биполярных клеток к амакриновым и далее к ганглионарным клеткам сетчатки [36,50].…”
Section: сетчаткаunclassified